Development of highly efficient Cu versus Pd catalysts supported on graphitic carbon materials for the reduction of 4-nitrophenol to 4-aminophenol at room temperature. (January 2017) - Morales, M.V.; Rocha, M.; Freire, C.; Asedegbega-Nieto, E.; Gallegos-Suarez, E.; Rodríguez-Ramos, I.; Guerrero-Ruiz, A.
Abstract: In this work we report a simple procedure for synthesis of Cu and Pd catalysts supported on high surface area graphite (HSAG) by wetness impregnation technique, and further generation of metal nanoparticles using NaBH4 as reducing agent. The catalysts have been tested in the reduction of 4-nitrophenol to 4-aminophenol, at room temperature, in presence of NaBH4 as hydrogen source. Both Cu and Pd catalysts exhibited exceptionally high catalytic activity with the total degradation of 4-nitrophenol in less than 45 s. Taking into account that Cu is cheaper than Pd, we focused our investigation on studying the catalytic properties of Cu nanoparticles supported over two lab prepared graphene-materials (one N-doped and other undoped) and the commercial HSAG. The maximum catalytic activity was obtained with Cu supported on undoped graphene due to the combination of two parameters: small metal particle size and the unique properties of graphene generated by its electron transference ability. However, recyclability of both Cu/graphene-materials fell after 5 consecutive runs, while Cu/HSAG displayed high stability even after 10 cycles. In order to rationalize these findings, it is postulated that copper nanoparticles in Cu/HSAG are located at the edges of the graphite layers, where a stronger metal-support interaction takes place. Graphical abstract: